Taxonomic investigation of selected rust fungi using scanning electron microscopy from Khyber Pakhtunkhwa, Pakistan. Issue 2 (27th September 2021) - Ijaz, Murtaza; Afza, Rabia; Zafar, Muhammad; Hamayun, Muhammad; Khan, Shujaul Mullk; Ahmad, Zeeshan; Ahmad, Mushtaq; Khan, Sumera Afzal; Shah, Raheem; Yahya, Muhammad
Abstract: Rusts comprises the largest natural group of plant pathogens including approximately 8% of all described Fungi. Rust fungi are extremely plant pathogens responsible for great losses to agriculture productivity. Rust species belong to several genera among which more than half are Puccinia species. In Pakistan, rust causes severe damage to agriculture crops. Current study was carried out to identify and characterize different rust species common in the research area through microscopy and Scanning electron microscopy (SEM) in Khyber Pakhtunkhwa, Pakistan. Morpho‐anatomical investigation of each collected rust species was carried out using different standard protocols. The dimensions of spores were measured and snapped under a stereomicroscope. SEM was used to examine the shape, size, and ornamentation of the spores of each rust fungus. Results revealed documentation of seven rust fungi, that is, Melampsora euphorbiae, Phragmidium barclayi, Puccinia nepalensis, P. exhausta, P. menthae, Uromyces capitatus, and Uromyces decorates belong to four different genera, were recorded. SEM revealed that spermogonia and Aecia were missing in most of the rust fungus studied. Uredinia was found in a scattered, irregular, lengthy, and epidermis‐enclosed form. Urediniospores were found to be ovulating, elongated, echinulate, globose to sub‐globose, ellipsoid to ovoid, and globose to sub‐globose. Telia was found as sub‐epidermal, amphigenous, dispersed, minute, and spherical cells. Teliospores ranged in form from cylindrical to oblong. The germ pores were detected in both apical (top cell) and basal (bottom cell) idiosyncratic and pedicel‐attached cells. The techniques used in the current investigation will aid mycologists in rust identification and microscopic characterization. Abstract : Identification and characterization of rust fungi using SEM. SEM comprehended that spermogonia and Aecia were mostly absent. Uredinia were present in dispersed, irregular, long, and enclosed by the epidermis. Teliospores were present from cylindrical to oblong in shape. This study will help rust identification and their microscopic characterizations.